THE THE HEPARIN INDUCED THROMBOCYTOPENIA IN CARDIAC SURGERY PATIENTS - Shakila Khadim (Army Medical College Rawalpindi, 2020)
Objective: Combination of ‘4Ts’ clinical scoring system and Particle gel immunoassay to determine the frequency of heparin-induced thrombocytopenia during heparin treatment in cardiac surgery patients.